Increasing Digital Marketing Effectiveness By Implementing Search Engine Optimization (SEO) In The Indonesian Banking Sector - Yudanegara, Aditya; Saputera, Denny; Muttaqin, Rizqi (Technium Business and Management, 2024)
This study evaluates the use of Search Engine Optimization (SEO) in digital marketing strategies within the Indonesian banking sector, specifically focusing on Bank Central Asia Tbk (BCA), Bank Mandiri Persero Tbk, and Bank Rakyat Indonesia Persero Tbk (BRI), during the period from February 2024 to April 2024. Employing an exploratory qualitative method, the research aims to gain an in-depth understanding of how these three banks implement SEO and how these strategies impact their customer engagement. The findings indicate that BCA utilizes Twitter as the primary platform for delivering rapid information, while Bank Mandiri and BRI prefer WhatsApp Web for direct and personal communication with customers. Additionally, BRI leverages video content on YouTube to enhance user engagement. The dominance of WhatsApp Web in social traffic for Bank Mandiri and BRI highlights the effectiveness of instant messaging platforms in building direct communication with customers. Conversely, Twitter proves effective in reaching a broader audience for BCA. This study emphasizes the importance of tailoring digital marketing strategies to suitable platforms to achieve specific business objectives and demonstrates the value of qualitative methods in understanding the dynamics and complexities of digital marketing within the banking sector.